The susceptibility of Anopheles lesteri to infection with Korean strain of Plasmodium vivax - Deepak Joshi (2018)
Background. Following its recent re-emergence, malaria has gained renewed attention as a serious infectious disease in Korea. Three species of the Hyrcanusgroup, Anopheles lesteri, Anopheles sinensis and Anopheles pullus, have long been suspected malaria vectors. However, opinions about their vector ability are controversial. The present study was designed with the aim of determining the susceptibility of these mosquitoes to a Korean isolate of Plasmodium vivax. Also, An. sinensis is primarily suspected to be vector of malaria in Korea, but in Thailand, the same species is described to have less medical importance. Therefore, comparative susceptibility of Thai and Korean strains of An. sinensis with Thai strain of P. vivax may be helpful to understand whether these geographically different strains exhibit differences in their susceptibility or not. Methods. The comparative susceptibility of An. lesteri, An. sinensis and An. pullus was studied by feeding laboratory-reared mosquitoes on blood from patients carrying gametocytes from Korea and Thailand. Results. In experimental feeding with Korean strain of P. vivax, oocysts developed in An. lesteri, An. sinensis and An. pullus. Salivary gland sporozoites were detected only in An. lesteri and An. sinensis but not in An. pullus. Large differences were found in the number of sporozoites in the salivary glands, with An. lesteri carrying much higher densities, up to 2,105 sporozoites in a single microscope field of 750 × 560 M, whereas a maximum of 14 sporozoites were found in any individual salivary gland of An. sinensis. Similar results were obtained from a susceptibility test of two different strains of An. sinensis to Thai isolate of P. vivax, and differences in vector susceptibility according to geographical variation were not detected. Conclusion. The high sporozoite rate and sporozoite loads of An. lesteri indicate that this species is highly susceptible to infection with P. vivax. Anopheles sinensis appears to have a markedly reduced ability to develop salivary gland infection, whilst in An. pullus, no sporozoites were found in the salivary glands. Provided that the survival rate of An. lesteri is sufficiently high in the field, it would be a highly competent vector of vivax malaria.